Gölem project: Concept and design of a trekking/hiking wheelchair - Gabriele Baronio; Alessandro Copeta; Barbara Motyl; Stefano Uberti (Advances in Mechanical Engineering, 2017)
This work concerns the growing interest in accessible tourism and describes the early stages of development of Gölem project. In particular, it takes into account accompanying activities of disabled people in mountain areas. Although literature and market analysis highlight the presence of different technical solutions used for the movement of disabled persons on rough terrains, there are only a couple of solutions based on the help of guides: Joëlette© and TrailRider©. Even if the use of these devices is generally satisfactory, our analysis has highlighted the presence of some limitations such as the difficulty of maintaining the lateral balance of the devices (which involves a considerable physical effort for the guides) and their reduced comfort for the passenger. This article describes the activities developed within the Gölem project. Its main goals are to design and to test an improved model of trekking/hiking wheelchair taking into account passengers comfort and better functionality of the device. At this moment, the design and modeling phases with the definition of dynamic parameters and of the suspension system of the device have been completed. The prototype implementation phase is in progress. Future activities will provide validation and field testing of the new solution with users.